Study of mechanical behavior by fatigue of a cracked plate repaired by different composite patches (Fracture and Structural Integrity, 2021)
This research is based on the study of the fatigue behavior of an aluminum alloy plate with a central crack. The plate is subjected to a tensile loading on its lower and upper parts. Several parameters were highlighted, such as the loading effect with a load ratio R = 0. The effects of the load ratio on both the repaired and not repaired plates, by two composite patches, which are boron/epoxy and graphite/epoxy, were investigated, as well as the effect of the plate material on plate life, comparing different materials
Keywords: Fatigue; Crack; Composite patch; Load ratio